0224 "The Image of Adam’s Glory" - Bogdan G. Bucur; Vladimir Ivanovici (RIHA Journal, 2019)
The imagery of the "radiant body" and "luminous garment" occurs frequently in early Christian references to the Edenic state of Adam and its partial reinstatement by Moses, Jesus, and numerous saintly (usually ascetic) figures. This article offers a synthetic presentation of these traditions, sketching out its main articulations, its biblical-exegetical foundations, its points of continuity with the apocalyptic traditions of the Second Temple Era and parallels with the Rabbinic tradition.